Induction of Apoptosis of Human Colon Cancer Cells by siRNA Recombinant Expression Vector Targeting Survivin Gene - 蔡明 王国斌 陶凯雄 蔡昌学 (Journal of Huazhong University of Science and Technology. Medical sciences, 2009)
This study constructed siRNA recombinant expression vector targeting survivin gene and observe the apoptosis induction effect of it in human colon cancer cells, siRNA recombinant expression vector targeting survivin gene was constructed and transfected into human colon cancer cells. The effect of siRNA recombinant expression vector was detected by RT-PCR, Western blot, MTT reduction assay and flow cytometry. It was confirmed by restriction endonuclease and sequence analysis that siRNA recombinant expression vector targeting survivin gene was constructed successfully. Inhibition rate of survivin siRNA at mRNA and protein levels was 36.33% and 44.65% respectively. Growth of cancer cells was inhibited and the apoptosis rate was （17.24±2.13）%. The siRNA recombinant expression vector targeting survivin gene has been constructed successfully. It not only can inhibit the expression of survivin gene, but also can induce apoptosis in human colon cancer cells remarkably.